2009
DOI: 10.1007/s10533-009-9310-3
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and forest management alter fungal-to-bacterial ratio and N2O-emission during rewetting in the forest floor and mineral soil of mountainous beech forests

Abstract: The effects of site exposure (microclimate) and forest management (thinning) on fungal-tobacterial (F:B) respiratory ratio and N 2 O emission from forest floor and Ah layer samples were studied at untreated and thinned beech forests. Microclimate effects were studied by selecting sites facing northeast (NE) or south-west (SW). The F:B respiratory ratio was estimated using substrate-induced respiration in combination with inhibitors either affecting fungi or bacteria. N 2 O production was evaluated after moiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…In view of the growing evidence on the role of fungal denitrification to N 2 O fluxes, the missing distinction between fungal and bacterial O exchange rates is relevant since it illustrates that variations in the fungal share of soil N 2 O fluxes would not affect the extent of O incorporation from H 2 O . Hence, the high O exchange during N 2 O formation in soil, as suggested by previous soil studies, is probably independent of the fungal‐to‐bacterial ratio of the N 2 O fluxes .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In view of the growing evidence on the role of fungal denitrification to N 2 O fluxes, the missing distinction between fungal and bacterial O exchange rates is relevant since it illustrates that variations in the fungal share of soil N 2 O fluxes would not affect the extent of O incorporation from H 2 O . Hence, the high O exchange during N 2 O formation in soil, as suggested by previous soil studies, is probably independent of the fungal‐to‐bacterial ratio of the N 2 O fluxes .…”
Section: Discussionmentioning
confidence: 88%
“…While research activities in earlier decades concentrated on bacterial denitrification processes, fungal denitrification has received more attention lately. Recent studies indicated that in some soils fungal N 2 O production from denitrification might even be greater than that of bacteria . However, the fungal production pathway of N 2 O has not yet been sufficiently investigated and to our knowledge there has been no study focusing on fungal oxygen (O) exchange between water (H 2 O) and denitrification intermediates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts suggested that fungi play a large but unrecognized role in N turnover and N 2 O flux (9,(11)(12)(13). Although the SIRIN methodology has provided valuable insight into the fungal contribution to denitrification, the application of SI-RIN to soils can be problematic as incomplete inhibition can bias the observations (14)(15)(16). Hence, alternative approaches (e.g., PCR) that selectively target fungal genes involved in denitrification are desirable to advance understanding of the fungal diversity contributing to N cycling in environments such as soils, aquifers, and deep-ocean sediments, where denitrifying fungi have been cultivated (7,13,17,18).…”
mentioning
confidence: 99%
“…In contrast, treatment M supplied organic matter, which can make organic molecules electron donors for denitrifiers to enhance denitrification. Previous research has shown that fungi prefer acidic conditions for denitrification and N 2 O emissions (Blagodatskaya, Dannenmann, Gasche, & Butterbach‐Bahl, ). However, Rohe et al () indicated that N 2 O emissions from fungal denitrification can occur at a neutral pH.…”
Section: Discussionmentioning
confidence: 99%